ANALISIS LAIK FUNGSI JALAN DALAM MEWUJUDKAN JALAN YANG BERKESELAMATAN - Deddy Riad; Renni Anggraini; Sofyan M. Saleh (JURNAL TEKNIK SIPIL, 2017)
Abstract:Soekarno-Hatta national road is one of the primary artery road that serves as the main axis that connects the center of national activities in the province. As one of the transport infrastructure plays an important role in the daily activities, the way that serves the public interest must be worhty as it relates to guarantee the certainty of safety and security for its users. The purpose of this study is Knowing whether Soekarno-Hatta Road has qualified Roadworthy so that it meets the technical requirements feasibility to provide safety for its users and to determine the category of Roadworthy. The methodology of this research was conducted based on the Rules of the Minister of Public Works No. 11 / PRT / M / 2010 on Procedures and Requirements of Roadworthy. From the survey results of the Roadworthy Test was obtained Worthy (LF) on I, II, IV and V of the Segment, while the status of the Worthy with Conditional (LS) was obtained in III and VI of the Segment. Recommendations to roadworthy conditions such as Routine Maintenance while on the Worthy with Conditional was  recommended to Rehabilitation Maintenance.Keywords : Road, Safety, Roadworthy.Abstrak: Jalan nasional Soekarno-Hatta merupakan salah satu jalan Arteri Primer yang berfungsi sebagai poros utama yang menghubungkan antar pusat kegiatan nasional di Provinsi Aceh. Sebagai salah satu prasarana transportasi yang memegang peranan penting dalam kegiatan sehari-hari, jalan yang melayani kepentingan umum harus laik fungsi karena berkaitan dengan penjaminan kepastian keselamatan dan keamanan bagi penggunanya. Tujuan penelitian ini adalah Mengetahui apakah Jalan Soekarno-Hatta telah memenuhi syarat Laik Fungsi Jalan sehingga memenuhi persyaratan teknis kelaikan untuk memberikan keselamatan bagi penggunanya serta menentukan kategori Laik Fungsi Jalan.  Adapun metodologi penelitian ini dilakukan dengan berpedoman kepada Peraturan Menteri Pekerjaan Umum Nomor : 11/PRT/M/2010 Tentang Tata Cara dan Persyaratan Laik Fungsi Jalan. Dari hasil survei Uji Laik Fungsi Jalan diperoleh status jalan kategori Laik Fungsi (LF) pada Segmen I, II, IV dan V sedangkan status jalan kategori Laik Fungsi Bersyarat (LS) didapat pada Segmen III dan VI. Rekomendasi terhadap kondisi jalan Laik  Fungsi berupa Pemeliharaan Rutin sedangkan pada kondisi jalan yang Laik Fungsi Bersyarat direkomendasikan Pemeliharaan Rehabilitasi.Kata kunci : Jalan, Keselamatan, Laik Fungsi Jalan.